Simulation of Particle-Fluid Interaction in Fractal Fractures Based on the Immersed Boundary-Lattice Boltzmann Method. (16th December 2020) - Liu, Shenggui; Tang, Songlei; Huang, Jinkuang; Lv, Mindong; Li, Yingjun
Abstract : In order to reveal the influence of particles on fluid flow characteristics in rough fractures under fluid-solid coupling, a range of fracture systems with varying roughness were generated using the Weierstrass-Mandelbrot function. Fluid-particle interactions in rough fractal fractures were simulated using the immersed boundary-lattice Boltzmann method. In this paper, the effects of fluid viscosity, particle size, particle quantity, fracture fractal dimension, and particle grading composition are studied. Results illustrate that increasing fluid viscosity hinders the movement of particles, resulting in the decreasing of particle velocity. As particle size and particle quantity increase, the particle occupation of the channel area grows larger, which lead to lower permeability of the channel. Increasing fracture fractal dimension surges the curvature of the fluid channel, but permeability has a negative exponential correlation to fractal dimension. With increasing particle grading composition, the blocking effect of particles on fracture flow also increases with increasing particle proportion.